Realist Ecstasy - Reckson, Lindsay (New York University Press, 2020)
Explores the intersection and history of American literary realism and the performance of spiritual and racial embodiment. Recovering a series of ecstatic performances in late nineteenth- and early twentieth-century American realism, Realist Ecstasy travels from camp meetings to Native American ghost dances to storefront church revivals to explore realism’s relationship to spiritual experience. In her approach to realism as both an unruly archive of performance and a wide-ranging repertoire of media practices—including literature, photography, audio recording, and early film—Lindsay V. Reckson argues that the real was repetitively enacted and reenacted through bodily practice. Realist Ecstasy demonstrates how the realist imagining of possessed bodies helped construct and naturalize racial difference, while excavating the complex, shifting, and dynamic possibilities embedded in ecstatic performance: its production of new and immanent forms of being beside. Across her readings of Stephen Crane, James Weldon Johnson, and Nella Larsen, among others, Reckson triangulates secularism, realism, and racial formation in the post-Reconstruction moment. Realist Ecstasy shows how post-Reconstruction realist texts mobilized gestures—especially the gestures associated with religious ecstasy—to racialize secularism itself. Reckson offers us a distinctly new vision of American realism as a performative practice, a sustained account of how performance lives in and through literary archives, and a rich sense of how closely secularization and racialization were linked in Jim Crow America.
10.18574/nyu/9781479803323.001.0001
Keywords: Anna Julia Cooper; Frances E. W. Harper; Ghost Dance; Hamlin Garland; James Mooney; James Weldon Johnson; Jim Crow; Nella Larsen; Pentecostalism; Reconstruction; W. E. B. Du Bois; William Dean Howells; William Van der Weyde; affect; body; capital punishment; conversion; electricity; ethnography; gesture; haunting; intersectionality; lynching; messiah craze; performance; photography; queerness; realism; recording; reenactment; secularism; secularization; settler colonialism; sexuality; storefront church; temporality; whiteness; American literature; Performance in literature; Race in literature; Realism in literature; Religion in literature; SOCIAL SCIENCE / Discrimination & Race Relations